2013
DOI: 10.6061/clinics/2013(sup01)01
|View full text |Cite
|
Sign up to set email alerts
|

The azoospermic male: current knowledge and future perspectives

Abstract: This special issue is fully dedicated to the topic of azoospermia and contains the seminal work of renowned scientists and clinicians from seven countries on three continents. In seventeen chapters, a comprehensive review of the epidemiology, genetics, physiopathology, diagnosis, and management of azoospermia addresses our current knowledge on the topic. The clinical results of assisted reproductive techniques applied to this category of male infertility and the health of offspring originating from such father… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 23 publications
0
21
0
5
Order By: Relevance
“…Infertile men can receive SSCs transplanted in their seminiferous tubules (Esteves & Agarwal, 2013). Being able to be reprogrammed into ES-like cells by human SSCs and murine leads to more differentiation into the derivatives of the three germ layers (Golestaneh et al, 2009).…”
Section: The Application Of Pluripotent Stem Cells For Testicular Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Infertile men can receive SSCs transplanted in their seminiferous tubules (Esteves & Agarwal, 2013). Being able to be reprogrammed into ES-like cells by human SSCs and murine leads to more differentiation into the derivatives of the three germ layers (Golestaneh et al, 2009).…”
Section: The Application Of Pluripotent Stem Cells For Testicular Cmentioning
confidence: 99%
“…However, ESCs have differentiation capability into male gametes in vitro or in vivo (He, 2012). Japanese scientists recently reported that they utilized mESCs to generate PGCs which, following testis transplantation, could differentiate into spermatozoa in mice (Aponte, Schlatt, & Franca, 2013;Esteves & Agarwal, 2013).…”
Section: Implications For Medicine In the Near And Further-off Futurementioning
confidence: 99%
“…Азооспермия и криптозооспермия являются наиболее тяжелыми формами патозооспер-мии. В подавляющем большинстве случаев азооспер-мия связана с рядом необратимых нарушений рабо-ты яичек, приводящих к угнетению сперматогенеза [6]. Такие нарушения чаще всего связаны с генетическими, эндокринными, а также с воспалительными заболева-ниями.…”
Section: Andrology and Genital Surgeryunclassified
“…[6][7][8] Non-Obstructive azoospermia (NOA) is associated with a spectrum of various severe and untreatable conditions associated with an intrinsic testicular impairment. 9 Parameters like history, physical examination, testicular volume and hormonal analysis (FSH, LH, TSH, Testosterone) and even the histology of a diagnostic biopsy are only indicative and not always predictive in diagnosing the cause of azoospermia because patients with maturation arrest (MA) generally have welldeveloped and normal-sized testes and normal hormonal levels. 10,11 Levels of FSH >7.6 mIU/ ml are found in about 89% of men with NOA but only if the levels are greater than twice the upper normal limit do they provide a reasonably precise diagnosis of testicular failure.…”
Section: Introductionmentioning
confidence: 99%